Malaise and remedy of binary boson-star initial data. (7th April 2022) - Helfer, Thomas; Sperhake, Ulrich; Croft, Robin; Radia, Miren; Ge, Bo-Xuan; Lim, Eugene A
Abstract: Through numerical simulations of boson-star head-on collisions, we explore the quality of binary initial data obtained from the superposition of single-star spacetimes. Our results demonstrate that evolutions starting from a plain superposition of individual boosted boson-star spacetimes are vulnerable to significant unphysical artefacts. For equal-mass binaries, these difficulties can be overcome with a simple modification of the initial data suggested in Helfer et al (2019 Phys. Rev. D 99 044046) for collisions of oscillations. While we specifically consider massive complex scalar field boson star models of very high and low compactness, we conjecture that this vulnerability be also present in other kinds of exotic compact systems and hence needs to be addressed.